Approaches to Culture in Foreign Language Teaching - MERROUCHE, Sarah (Journal of Human Sciences, 2010)
Language and culture are inextricably tied: they cannot be separated without losing their essence and significance. What is language if not a means of communication operating in a defined socio-cultural context? Without language, communication would be very restricted; without culture, there would be no communication at all. A crucial implication is that one cannot be taught without the other. Notwithstanding the inseparability of language and culture, the foreign culture is not always welcome in the foreign language class. Some teaching professionals put forward heated arguments against incorporating it in language curricula and textbooks. Others believe it to be a ‘taken-for-granted’ component in foreign language pedagogy, for several other arguments. The object of this paper is to shed light on the place of culture in the foreign language class, drawing on seminal works in the field of language and culture teaching / learning. Adopting a convincing stance towards this issue is, no doubt, a prerequisite for effective teaching / learning.